Opportunity or necessity entrepreneurship? A study based on the national system of entrepreneurship - Yangjie Huang; Ping Li; Lu Chen; Jing Wang (Journal of Innovation & Knowledge (JIK), 2023)
This study investigates synergies between individual and national variables that promote opportunity and necessity entrepreneurship with a framework based on the national system of entrepreneurship. A qualitative comparative analysis of fuzzy sets of 39 country cases shows that institutional or individual cognitive elements are not necessary for high-opportunity or high-necessity entrepreneurship but that enhancing entrepreneurs' ability perceptions play a universal role. The study's findings reveal optimal pathways that combine the institutional environment and individual perceptions to promote the synergistic development of opportunity and necessity entrepreneurship and reduce differences in entrepreneurial activities between countries.
Keywords: I25; L26; J68; 650; National system of entrepreneurship; Necessity entrepreneurship; Opportunity entrepreneurship; NCA; FsQCA